1987
DOI: 10.1111/j.1399-6576.1987.tb02597.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐related effects of isoflurane on superior mesenteric vasoconstriction induced by endotoxemia in the rat

Abstract: To investigate the interplay between endotoxin-induced circulatory shock and the cardiovascular effects of different doses of isoflurane, mean aortic pressure (MAP), central venous pressure (CVP), mean pulmonary arterial pressure (MPAP), heart rate (HR), cardiac output and superior mesenteric artery flow (SMAF), were monitored in rats anesthetized with either 1.4% or 2.0% isoflurane in oxygen. Cardiac index (Cl), total peripheral vascular resistance (TPR) and superior mesenteric vascular resistance (SMVR) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This particular model of endotoxemia was developed to manifest a hyperdynamic response (increased cardiac output and decreased systemic vascular resistance) similar to the initial stage of shock found in human sepsis and has been the model chosen for other studies of sepsis hemodynamics (1,22). However, we believe that this is the first study to exploit the characteristics of this nonlethal sepsis model in the conscious animal, eliminating depression or alteration of cardiovascular and metabolic function and compensatory responses associated with the use of anesthesia (5,55,56). The hyperdynamic response in this particular conscious-rat model of sepsis is transient, occurring during the first hour, and is immediately followed by a hypodynamic response characterized by decreased cardiac output and stroke volume and increased systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This particular model of endotoxemia was developed to manifest a hyperdynamic response (increased cardiac output and decreased systemic vascular resistance) similar to the initial stage of shock found in human sepsis and has been the model chosen for other studies of sepsis hemodynamics (1,22). However, we believe that this is the first study to exploit the characteristics of this nonlethal sepsis model in the conscious animal, eliminating depression or alteration of cardiovascular and metabolic function and compensatory responses associated with the use of anesthesia (5,55,56). The hyperdynamic response in this particular conscious-rat model of sepsis is transient, occurring during the first hour, and is immediately followed by a hypodynamic response characterized by decreased cardiac output and stroke volume and increased systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 92%
“…An effect or the lack of an effect on blood pressure alone is insufficient to make definitive conclusions regarding the cardiovascular system since normal blood pressures can occur in the presence of either high or low cardiac output depending on the status of the vascular system. Other studies using a similar model (1,22) have reported changes in these parameters which may have been due to the influence of anesthesia on the cardiovascular system and the effectiveness of compensatory responses during cardiovascular challenge (5,55,56).…”
Section: Discussionmentioning
confidence: 95%